Τhe perceptions of teachers regarding the use of the English language in teaching Mathematics and science: a study in Johore - Zainuddin, Ruhana; A. Hamid, Maznah (Institut Pengurusan Penyelidikan, Pembangunan & Pengkomersilan, 2004)
The purpose of this study was to investigate the perceptions of teachers regarding the use of the English language in teaching Mathematics and Science in schools. The sample consisted of 548 teachers from eighteen selected schools in the state of Johor. The study examined the effect of the teachers' socio-demographic backgrounds on their perceptions toward the policy. The findings revealed that perceptions were both positive and negative. Additionally, the relationship between teachers' acceptance and their perceptions was investigated. The statistical tests utilized included the independent samples t-test, ANOVA, and multiple regression analysis. The results indicated that while teachers generally agreed with the policy proposed by the government, they held specific perceptions regarding its implementation. Furthermore, the teachers' socio-demographic backgrounds were found to have an impact on their perceptions.